A Comprehensive Study on the Effects of the Boundary Conditions on the Elastic Buckling Capacity of a Perforated Plate - Sadegh Ghorbanhosseini; Saeed Yaghoubi; Mohammad Reza Bahrambeigi (International Journal of Advanced Design and Manufacturing Technology, 2021)
Nowadays, different industries are using sheets, plates, and shells as important parts of their components. Because of their small thickness compare to other dimensions, their structural safety requires more attention. Therefore, increasing their strength and intensifying their resistance against any kind of failure type could be introduced as an important problem for enhancing the structural safety. Buckling is one of the most significant failure type that should be considered in the stability of any parts such as sheet metals. Thus, investigation of the buckling capacity of the sheet metals is remarkable. On the other hand, the existence of discontinuity like holes and notches in sheet metals can decrease their buckling capacity, significantly. In current study, based on Finite Element Method (FEM), ABAQUS/Explicit has been employed to determine the elastic buckling capacity in a perforated rectangular sheet metal with different boundary conditions on its edges. Afterward, the effect of the hole position and the plate aspect ratios (plate length/plate width) on the buckling capacity of sheet metal was studied. Finally, in order to enhance the sheet metal buckling capacity, two different types of stiffeners were used. The outcomes showed that the maximum buckling coefficient is related to the sheet metal which have four clamped edges. Moreover, For all boundary conditions, the buckling coefficient does not change significantly for the sheet metals with aspect ratio of more than 4. Also, stiffener type 2 increased the buckling capacity of sheet metal up to 83%.